On weakly m-convex sets - Dakhil H. К.; Zelinskii, Yu. B.; Klishchuk B. А. (Reports of the National Academy of Sciences of Ukraine, 2017)
Some properties of weakly m-convex sets are studied. Various variants of the problem of shadow are investigated. The lower bound for the number of balls that are necessary to create a shadow at a point tangential to sphere S2 in the Euclidean space R3, is obtained.